Mixed-Convective Processes Within Seafloor Sediments Arising From Fresh Groundwater Discharge - Solórzano-Rivas, S. C.; Werner, Adrian D.; Irvine, Dylan J. (Frontiers in Environmental Science, 2021)
The dependence of near-shore ecosystems on the freshwater component of submarine groundwater discharge (SFGD) is well recognized. Previous studies of SFGD have typically assumed that SFGD occurs through aquitards that are in direct contact with seawater. These studies provide no guidance on the distribution of freshwater discharge to the seafloor where SFGD occurs through sandy sediments, even though in most situations, seabed sediments are permeable. We find that SFGD may occur in unconfined, seafloor sediments as density-driven flow in the form of fingers, or otherwise, diffusive freshwater discharge is also possible. Unstable, buoyancy-driven flow within seabed sediments follows similar patterns (except inverted) to the downward free convection of unstable (dense over less-dense groundwater) situations. Consequently, the same theoretical controlling factors as those developed for downward mixed-convective flow are expected to apply. Although, there are important differences, in particular the boundary conditions, between subsea freshwater-seawater interactions and previous mixed-convective problems. Simplified numerical experiments in SEAWAT indicate that the behavior of fresh buoyant plumes depends on the aquifer lower boundary, which in turn controls the rate and pattern of SFGD to the seafloor. This paper provides an important initial step in the understanding of SFGD behavior in regions of sandy seafloor sediments and analyses for the first time the mixed-convective processes that occur when freshwater rises into an otherwise saline groundwater body.